Expatriates Perceptions toward Hofstede’s Indonesia Cultural Dimensions - Damar Aji Irawan (Bina Nusantara University, 2017)
The purpose of this research was to explore the experiences of expatriates in Indonesia, related to Hofstede’s Indonesia cultural dimensions. This study applied a phenomenological qualitative study and used purposive sampling to select the participants. Data were gathered using the semi-structured interview with appointments set before the meeting. The interviews were conducted on an individual basis and were recorded. Then, the data were transcribed and analyzed through coding and categorizing until sets of themes occurred. The results show that the majority of participants agree Indonesia has collectivism and low uncertainty avoidance culture. Meanwhile, the expatriates’ experiences toward high power distance dimension in Indonesia vary.